Autosomal rearrangement in Gryllus assimilis Fabricius, 1775 (Orthoptera, Gryllidae) - Zefa,Edison (1999)
Gryllus assimilis L. has a karyotype of 2n = 29 (X0, male) and 30 (XX, female). The above karyotype was encountered along with another in which 2n = 28 (X0, male) and 2n = 29 (XX, female) in a population from the outskirts of Rio Claro city (São Paulo State, Brazil). Of eight specimens studied, five had the heterozygous karyotype involving a translocation and three had the basic karyotype. There were no individuals homozygous for the rearrangement. The heterozygous karyotype was the result of a chromosomal rearrangement between chromosome pairs 6 and 10, both of which were initially submetacentric. The members of the sixth pair normally have two constrictions in the small arm, with a satellite at the chromosome tip. The chromosome of the tenth pair involved in the translocation was generally submetacentric and probably underwent a pericentric inversion which transported the centromere to a subterminal position before being translocated. In this case, the long arm of the inverted chromosome of the tenth pair was translocated with the satellite of a member of the sixth pair.